Respuesta :
Answer:
d = √34
Step-by-step explanation:
(-2, -1) & (3, 2)
d = √[(x₂ - x₁)² + (y₂ - y₁)²]
d = √[(3 + 2)² + (2 + 1)²]
d = √[(5)² + (3)²]
d = √(25 + 9)
d = √34
Answer: A. √34
Step-by-step explanation:
I had the same problem
![Ver imagen isabellamejias2010](https://us-static.z-dn.net/files/dd5/a02df980f3ef5564de9cc17743723f40.jpeg)
![Ver imagen isabellamejias2010](https://us-static.z-dn.net/files/d78/47c720ca699818bf3f1533a2910f099e.jpeg)
![Ver imagen isabellamejias2010](https://us-static.z-dn.net/files/de5/12ee7d63b99c05591c62e7507ce3896e.jpeg)
![Ver imagen isabellamejias2010](https://us-static.z-dn.net/files/de3/c6def3c07f6e63a7c39e946d2b6b78bd.gif)
Answer:
d = √34
Step-by-step explanation:
(-2, -1) & (3, 2)
d = √[(x₂ - x₁)² + (y₂ - y₁)²]
d = √[(3 + 2)² + (2 + 1)²]
d = √[(5)² + (3)²]
d = √(25 + 9)
d = √34
Answer: A. √34
Step-by-step explanation:
I had the same problem